30 years of service for the health of children: we teach, we treat, we write, we create - N. V. Skripchenko (LLC "Diagnostics and Vaccines", 2021)
The article, dedicated to the 30th anniversary of the founding of the Department of Infectious Diseases in Children of the Faculty of Postgraduate and Additional Professional Education of the St. Petersburg State Medical Pediatric University of the Ministry of Health of Russia, outlines the history of the creation and development of the department. The results of the comprehensive activities of the department are reflected: educational, research, organizational and methodological, treatment and diagnostic and advisory. The main directions and results of scientific work, their effectiveness when introduced into practical health care are described. The educational-methodical developments of the department, published in recent years, are presented, which are an important tool for improving the professional level of doctors. It is noted that by increasing the educational level of medical personnel, the department contributes to improving the quality of medical care for children, thereby not only taking part in improving the demographic situation in the country, but also in ensuring its national security.